Hold the line: The evolution of telecommunications provisions in regional trade agreements - José-Antonio Monteiro (World Trade Organization (WTO), 2021)
Based on the first comprehensive mapping of telecommunications provisions telecommunications in regional trade agreements (RTAs), this paper shows that telecommunications provisions in RTAs have evolved and expanded significantly over the years. While some provisions focus on information and communications technologies (ICT) infrastructure, policy and investment, other provisions address telecommunications services as well as standards and conformity assessment procedures of ICT equipment. The most detailed and comprehensive telecommunications provisions are found in stand-alone chapters, sections or annexes on telecommunications services. A network analysis further reveals that telecommunications provisions remain highly heterogenous. Only a limited number of, mostly advanced economies, tend to negotiate very detailed and comprehensive provisions on telecommunications in their respective RTAs. While many telecommunications provisions found in RTAs draw on existing WTO rules, including the Annex on Telecommunications to the General Agreement on Trade in Services (GATS), some GATS provisions, the Reference Paper on Regulatory Principles on Basic Telecommunications and the Agreement on Technical Barriers to Trade, an increasing number of RTAs incorporate explicit provisions that expand existing WTO disciplines and address new regulatory topics related to telecommunications services, such as international roaming, net neutrality, and stolen or lost mobile terminal equipment.
Keywords: F13; F15; 330; World Trade Organization; Regional Trade Agreements; Telecommunications; Digitaleconomy; Network Analysis